AZT as a telomerase inhibitor - Gomez, Daniel E.; Armando, Romina G.; Alonso, Daniel F. (Frontiers in Oncology, 2012)
Telomerase is a highly specialized reverse transcriptase and the maintenance of telomeric length is determined by this specific enzyme. The human holoenzyme telomerase is a ribonucleoprotein composed by a catalytic subunit, hTERT, an RNA component, hTR, and a group of associated proteins. Telomerase is normally expressed in embryonic cells and is repressed during adulthood. The enzyme is reexpressed in around 85% of solid tumors. This observation makes it a potential target for developing drugs that could be developed for therapeutic purposes. The identification of the hTERT as a functional catalytic reverse transcriptase prompted studies of inhibiting telomerase with the HIV reverse transcriptase inhibitor azidothymidine (AZT). Previously, we have demonstrated that AZT binds preferentially to telomeres, inhibits telomerase and enhances tumor cell senescence and apoptosis after AZT treatment in breast mammary adenocarcinoma cells. Since then, several studies have considered AZT for telomerase inhibition and have led to potential clinical strategies for anticancer therapy. This review covers present thinking of the inhibition of telomerase by AZT and future treatment protocols using the drug.